Comparative feedlot performance and carcass characteristics of Sudanese desert sheep and goats - El-Khidir, I.A.; Babiker, S.A.; Shafie, S.A. (Elsevier, 1998)
Under similar levels of feeding, desert sheep grew faster and reached slaughter weight of 35 kg in a significantly (p